Pemanfaatan Metode AIDA Dalam Desain Website Sebagai Media Promosi Produk Pada UMKM - Andik Prakasa Hadi; Ahmad Zainudin; Nuris Dwi Setiawan (Teknik Komputer Politeknik Negeri Sriwijaya, 2021)
KISS Semarang is an UMKM located in Mangunharjo, established in 2010. “KISS” Semarang MSME has done media promotions by distributing brochures. However, it is not optimal in its promotional media. A product catalog in the business world is a medium that serves to promote goods sold to attract buyers, in the business world a catalog is very important because it is more efficient to promote the products offered. The design of the website design in this study uses the AIDA analysis method: Attention, Interest, Desire, Action. In this study, the authors set KISS Semarang as the research subject, the data obtained for research needs using techniques such as interviews, observations, questionnaires and literature studies. The results showed that in field trials, website design was useful and could be used to promote products.